Atypical Presentation of Two Chikungunya Cases: A Case Series during 2025 Outbreak - Hossain, Zazeba; Ahmed, Asif; Raka, Farzana Afroz; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2025)
Bangladesh is experiencing a sharp rise in viral infections, particularly during the current monsoon season. Dengue, chikungunya, and COVID-19 are now posing a triple threat to public health. As their symptoms are overlapping, a strong diagnostic support is pivotal in severe cases.Here, we describe two older male chikungunya virus patients who, in addition to their typical symptoms, have significant organ involvement. Pneumonia caused by chikungunya affecting the lungs occurred in the first patient. The second case had similar lung involvement with encephalitis. Both had diabetes and hypertension, two co-morbidities that increase the chance of developing serious illness. The second case was also a known case of chronic kidney disease (CKD), old cerebrovascular disease (CVD) and ischaemic heart disease (IHD). He was transferred to the critical care unit and eventually passed away. These cases demonstrate how crucial it is that Chikungunya PCR tests be made available across the country at a reasonable cost in order to prevent needless treatment and investigations as well as early case diagnosis. Bangladesh J Medicine 2025; 36(3): 147-154